Meeting of Catholicos of All Armenians Matteos II Izmirlyan with Russian Emperor Nicholas II - Mikayelyan, Mikayel (History and Culture, 2021)
The tragedy in Adana in 1909 was planned by the Young Turks in the Ottoman Empire and in these terrible days Nicholas II published a manifesto according to which the Armenian Patriarch of Constantinople Matteos Izmirlyan became the Catholicos of All Armenians, after which the Catholicos, arriving in Russia, immediately went to St. Petersburg to meet with the Russian emperor, where he voiced the problem of Western Armenians, noted that he didn’t believe that the pogroms of Armenians could stop in the Ottoman Empire. In our opinion, Matteos II had an information that the Young Turks were behind the tragedy in Adana.We can state that during the meeting of Nicholas II and Matteos II, there was no mention of the problems of Eastern Armenians, only the problem of Western Armenians was touched upon, where the Catholicos raised the issue of mass pogroms, but the information that reached us didn’t mention support and sponsorship from the Russians.
Keywords: Matteos II Izmirlyan; Nicholas II; Pyotr Stolypin; Mehmed Reshad V; Constantinople; Adana; the Young Turks; St. Petersburg; Peterhof Palace; Western Armenian and Eastern Armenian press